Sense Relations Analysis of Homonymy in The Tragedy of Macbeth (2021) Screenplay - Alamsyah, Alamsyah; Wulandari, Kevin Olyvia (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The Tragedy of Macbeth raises the issue of power struggles and bloodshed which causes the main character to experience paranoia, hallucinations, and talk to himself. In this film, the utterances spoken by several characters use unique diction, which tends to be strange, and can make the audience question the meaning of the utterance. In everyday life nor in the academic environment, there are often misunderstandings of meaning by the speaker and the listener. In the realm of linguistics, semantics which is the science of meaning, plays an important role in classifying the meaning intended by the speaker. This research focuses on the use of homonyms from the characters of The Tragedy of Macbeth (2021) film using Kreidler's theory about sense relations, especially homonyms which is used as the main theory in this research. The data were taken from the screenplay of The Tragedy of Macbeth using descriptive qualitative methods with a semantic approach to sense relations. The researcher found that the homonymy indicates that the characters in the objective digress a lot in communication which can cause any misinterpretation. The occurrence of homonymy can be caused by the development of meaning that spreads, the influence of foreign words in the language or also for communication needs. Sense relations theory can conclude that a word can be interpreted more specifically depending on the context in which it occurs. In this research, sense relations played a role in the discovery of homonyms, homophones, and homographs in the objective.